Melatonin for sleep problems in children with neurodevelopmental disorders: randomised double masked placebo controlled trial. (5th November 2012) - Gringras, P; Gamble, C; Jones, A P; Wiggs, L; Williamson, P R; Sutcliffe, A; Montgomery, P; Whitehouse, W P; Choonara, I; Allport, T; Edmond, A; Appleton, R
Abstract : Objective To assess the effectiveness and safety of melatonin in treating severe sleep problems in children with neurodevelopmental disorders. Design 12 week double masked randomised placebo controlled phase III trial. Setting 19 hospitals across England and Wales. Participants 146 children aged 3 years to 15 years 8 months were randomised. They had a range of neurological and developmental disorders and a severe sleep problem that had not responded to a standardised sleep behaviour advice booklet provided to parents four to six weeks before randomisation. A sleep problem was defined as the child not falling asleep within one hour of lights out or having less than six hours' continuous sleep. Interventions Immediate release melatonin or matching placebo capsules administered 45 minutes before the child's bedtime for a period of 12 weeks. All children started with a 0.5 mg capsule, which was increased through 2 mg, 6 mg, and 12 mg depending on their response to treatment. Main outcome measures Total sleep time at night after 12 weeks adjusted for baseline recorded in sleep diaries completed by the parent. Secondary outcomes included sleep onset latency, assessments of child behaviour, family functioning, and adverse events. Sleep was measured with diaries and actigraphy. Results Melatonin increased total sleep time by 22.4 minutes (95% confidence interval 0.5 to 44.3 minutes) measured by sleep diaries (n=110) and 13.3 (−15.5 to 42.2) measured by actigraphy (n=59). Melatonin reduced sleep onset latency measured by sleep diaries (−37.5 minutes, −55.3 to −19.7 minutes) and actigraphy (−45.3 minutes, −68.8 to −21.9 minutes) and was most effective for children with the longest sleep latency (P=0.009). Melatonin was associated with earlier waking times than placebo (29.9 minutes, 13.6 to 46.3 minutes). Child behaviour and family functioning outcomes showed some improvement and favoured use of melatonin. Adverse events were mild and similar between the two groups. Conclusions Children gained little additional sleep on melatonin; though they fell asleep significantly faster, waking times became earlier. Child behaviour and family functioning outcomes did not significantly improve. Melatonin was tolerable over this three month period. Comparisons with slow release melatonin preparations or melatonin analogues are required. Trial registration ISRCT No 05534585.